Optimalisasi Komunitas Guru Dalam Peningkatan Kinerja Dan Mutu Pengajaran Di Sekolah Penggerak - Syamsuariadi, Syamsuariadi; Adam, Adam; Lilianti, Lilianti (Universitas Negeri Makassar, 2025)
This study aims to analyze the optimization of teacher communities in improving the performance and quality of teaching in pilot schools in North Kolaka Regency. Furthermore, this study also examines the strategies implemented by teacher communities and the impact of their involvement on improving the quality of education. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and document analysis involving teachers, principals, and relevant stakeholders. The results indicate that optimization of teacher communities is carried out through continuous professional development programs, collaboration between teachers, and the use of technology in learning. The strategies implemented include regular training, group discussions, and peer mentoring to improve pedagogical competence and professionalism. The impact of teacher community involvement includes increased teaching motivation, innovation in learning strategies, and improved student learning outcomes. This study recommends strengthening school policies to support teacher communities and integrating collaborative practices to improve teaching effectiveness in pilot schools in North Kolaka Regency.